Principal's Perception of the Performance of Physical Education Teachers for Sports and Health MGMP SMP in Bengkulu City - Bogy Restu Ilahi; Rambat Nur Sasongko; Muhammad Kristiawan; Tri Turnadi (UNIB Press, 2021)
This study aims to determine the performance of PJOK teachers who have participated in the MGMP organization (subject teacher deliberation). The research subjects involved the principals of junior high schools in Bengkulu City totaling 24 students. Instruments and techniques for collecting data were questionnaires. The data analysis technique used qualitative descriptive analysis as outlined in the form of a percentage. Based on the results of the analysis of the research data above, it can be seen that the Principal's Perception of the Teacher Performance of PJOK MGMP SMP in Bengkulu City has a very good perception of Pedagogic competence with a percentage (77.78%), Principal's good perception of Personality competence with a percentage (76.64%), a good perception of professional competence with a percentage (75.14%), and a good perception of social competence with a percentage (76.14%) So it can be concluded that the Principal's Perception of PJOK Teacher Performance MGMP SMP in Bengkulu City has good criteria with a percentage (76.42%).